Evaluation of Hospital Management Information System Implementation with the Delon and Mclean Method at RSUD dr. Doris Sylvanus Central Kalimantan: Evaluasi Implementasi Sistem Informasi Manajemen Rumah Sakit Dengan Metode Delon and Mclean Di RSUD dr. Doris Sylvanus Kalimantan Tengah - Hidayah, Nani; Wariyanti, Astri Sri; Sutrisno, Trismianto Asmo (Procedia of Engineering and Life Science, 2025)
The Hospital Information System (SIMRS) at RSUD Dr. Doris Sylvanus has been operational since 2021. However, based on a preliminary study, several challenges were identified, including poorly stored data and user formats that do not comply with the standardized SIMRS format. The aim of this research is to evaluate the implementation of SIMRS using the Delone and McLean method at RSUD Dr. Doris Sylvanus. The research design is an analytical observational study with a cross- sectional approach. The population of this study consists of all SIMRS users, totaling 1008 users. The sample size is determined to be 91 users using the Slovin formula. Data collection is conducted through questionnaires, and data analysis is performed using the correlation product-moment test. The research findings indicate a significant influence of system quality, information quality, and service quality on user satisfaction. Furthermore, there is a significant impact of user satisfaction on net benefits, and there is a significant influence of net benefits on user satisfaction. In conclusion, this research reveals the influence of system quality, information quality, and service quality on SIMRS user satisfaction, along with the relationship between user satisfaction and net benefits. The researcher recommends that RSUD Dr. Doris Sylvanus conducts socialization activities to improve user satisfaction with the system.